2022
DOI: 10.3389/fphar.2022.903978
|View full text |Cite
|
Sign up to set email alerts
|

Kappa Opioid Receptor Blockade in the Amygdala Mitigates Pain Like-Behaviors by Inhibiting Corticotropin Releasing Factor Neurons in a Rat Model of Functional Pain

Abstract: Functional pain syndromes (FPS) occur in the absence of identifiable tissue injury or noxious events and include conditions such as migraine, fibromyalgia, and others. Stressors are very common triggers of pain attacks in various FPS conditions. It has been recently demonstrated that kappa opioid receptors (KOR) in the central nucleus of amygdala (CeA) contribute to FPS conditions, but underlying mechanisms remain unclear. The CeA is rich in KOR and encompasses major output pathways involving extra-amygdalar p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 89 publications
3
27
0
1
Order By: Relevance
“…The next part of the work is based on a study which found that blocking kappa opioid receptors in the amygdala leads to a decrease in the spike activity of pyramidal neurons [19]. A similar effect was observed when blocking CRF1 receptors, which, like kappa-opioid receptors, exert their effects through the beta-arrestin pathway and the activation of MAPK p38 [20].…”
Section: Resultsmentioning
confidence: 99%
“…The next part of the work is based on a study which found that blocking kappa opioid receptors in the amygdala leads to a decrease in the spike activity of pyramidal neurons [19]. A similar effect was observed when blocking CRF1 receptors, which, like kappa-opioid receptors, exert their effects through the beta-arrestin pathway and the activation of MAPK p38 [20].…”
Section: Resultsmentioning
confidence: 99%
“…In a spinal nerve ligation (SNL) model of pain, nor-BNI in the right CeA blocked conditioned place preference (CPP) driven by gabapentin (an FDA approved treatment for neuropathic pain), suggesting that CeA KOR signaling is necessary for pain-induced negative affect ( Navratilova et al, 2019 ). Further, intra-CeA KOR antagonism blocks anxiety-like behavior and ultasonic vocalizations in a rat functional pain model wherein morphine priming sensitizes stress-induced pain-like and affective behavior ( Yakhnitsa et al, 2022 ). Moreover, increased CeA Dyn signaling may shape pain-related behavior as intra-CeA KOR antagonism blocks defensive behaviors in response to noxious stimuli using Randall Selitto to measure the paw withdrawal threshold ( Phelps et al, 2019 ) or sensitivity to capsaicin left forepaw injection in a functional pain model involving morphine priming in rats exposed to a bright light stimulus ( Nation et al, 2018 ).…”
Section: Regulation Of Pain By Amygdala Dynorphin/kappa Opioid Recept...mentioning
confidence: 99%
“…Furthermore, electrically evoked IPSCs onto CeA neurons are only potentiated by nor-BNI in SNL rats but not sham controls ( Navratilova et al, 2019 ). Moreover, PBN-evoked polysynaptic inhibition or electrically-evoked IPSCs are potentiated by nor-BNI in the functional pain model described above ( Yakhnitsa et al, 2022 ). These studies suggest that heightened Dyn signaling may be contributing to CeA neuron disinhibition in pain states.…”
Section: Regulation Of Pain By Amygdala Dynorphin/kappa Opioid Recept...mentioning
confidence: 99%
“…Furthermore, the optoinhibition of CRF containing neurons in CeA is sufficient to impair anxiety-like behaviour induced by pain (Hein et al, 2021;Mazzitelli et al, 2022). Interestingly, KOR blockade in CeA controls pain-related behaviour in a model of functional pain by restoring synaptic inhibition of CeA-CRF neurons, demonstrating that KOR and CRF systems are closely related in pain and its comorbidities (Yakhnitsa et al, 2022). However, most of these cited papers have obtained these results only in male rodents leaving females understudied.…”
Section: Introductionmentioning
confidence: 99%